Managing target costs at the development stage of a product - Todić, Vladimir; Maksimović, Rado; Ćosić, Ilija (Journal of Production Engineering, 2020)
At the development stage of a product, target cost management has a significant effect on achievement and maintenance of product competitiveness in a given market and the desired target profit as the primary aim of production. Target cost management, i.e., target profit management, is performed by evaluating individual variations of a conceptual and preliminary design solution for a new product and by choosing the solution with the lowest development costs. The paper presents the use of Adaptive Neural Fuzzy Inference System model for managing development costs on the example of double-row angular contact ball bearings as an example of applying the above approach to market positioning in relation to competitors.